The Ulama and The State Politics During Pandemic: A Study on the Covid-19 Related Fatwa of the Council of Indonesian Ulama - Anshor, Ahmad Muhtadi (Dialogia, 2023)
This study examines the contemporary dynamics of the relationship between the Council of Indonesian Ulama (Majelis Ulama Indonesia/MUI) and the Indonesian government. As far as the MUI is concerned, the council has experienced a changing position concerning the Indonesian state relationship, from being the custodian of the government (khādim al-ḥukūma) to the custodian of the Indonesian Muslim community (khādim al-umma). This changing position appears mainly through MUI legal opinion (fatwās). Considering the current situation in Indonesia, where the Covid-19 pandemic has stormed, this article analyzes the relationship between MUI and the government. It examines MUI's fatwās issued during the pandemic, especially those related to public worship, economy, and health. This article argues that MUI's related fatwās on Covid-19 indicate a new turnback with MUI and the Indonesian state relationship. The fatwas show a strong direction that MUI leads to the position of khādim al-ḥukūma rather than khādim al-umma.